PENGARUH KARAKTER WIRAUSAHA TERHADAP KEBERHASILAN USAHA MELALUI LITERASI KEUANGAN (Studi Kasus pada UMKM Kuliner Kecamatan Wonodadi Kabupaten Blitar) (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
Entrepreneurship is the result of discipline through a systematic process of implementing creativity and innovation in meeting market needs and opportunities. An entrepreneur is a person who pursues achievement, dares to take risks. The better the understanding of a person's financial literacy, the better his financial management will be. Financial literacy has an impact on almost all aspects related to planning and spending money such as income, savings, investments etc. Thus, whether the characteristics of entrepreneurship and financial literacy will affect the business success of Culinary MSME in Wonodadi District, Blitar Regency. The research method used is quantitative research. This study will explain the influence of Entrepreneurial Character (X1) and Financial Literacy (X2) as an intervening variable on business success (Y) of Culinary MSME Entrepreneurs in Wonodadi District, Blitar Regency. The results of the analysis show that the entrepreneurial character and financial literacy have a significant effect on business success (Y) either simultaneously or partially. Financial literacy has a significant effect on the success of the Culinary MSME business in Wonodadi District, Blitar. The results of the analysis show that financial literacy has a small indirect effect. This means that the majority of Culinary MSME businessmen in Wonodadi District, Blitar are still not optimal in understanding financial literacy.